2013
DOI: 10.1021/nn3053439
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal In Vivo Imaging Exposes the Voyage of Nanoparticles in Tumor Microcirculation

Abstract: Tumors present numerous biobarriers to the successful delivery of nanoparticles. Decreased blood flows and high interstitial pressures in tumors dictate the degree of resistance to extravasation of nanoparticles. To understand how a nanoparticle can overcome these biobarriers, we developed a multimodal in vivo imaging methodology, which enabled the non-invasive measurement of microvascular parameters and deposition of nanoparticles at the microscopic scale. To monitor the spatiotemporal progression of tumor va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 49 publications
1
66
0
1
Order By: Relevance
“…In addition to differences in total uptake, early variations in intratumoral localization were clearly visible and were probably caused by perfusion differences (24,25). For example, MDA-MB-231 showed a clear uptake in certain regions of the tumor periphery, whereas other regions remained clear.…”
Section: In Vivo Localization Of 111 In-labeled Liposomes In Human Tumentioning
confidence: 99%
“…In addition to differences in total uptake, early variations in intratumoral localization were clearly visible and were probably caused by perfusion differences (24,25). For example, MDA-MB-231 showed a clear uptake in certain regions of the tumor periphery, whereas other regions remained clear.…”
Section: In Vivo Localization Of 111 In-labeled Liposomes In Human Tumentioning
confidence: 99%
“…Another study found that a nanoparticle’s size dictates the extent to which blood flow affects its transport. A threefold increase in blood flow resulted in a 100-fold elevated intratumoral deposition of PEGylated liposomes with a hydrodynamic diameter of 100 nm [30] (Fig. 3).…”
Section: Engineering Targeted Nanoparticles For Cancer Imagingmentioning
confidence: 99%
“…While nanoparticle CT agents are excellent blood pool agents [30, 154], the development of targeted CT probes has been limited due to the low contrast sensitivity of the X-ray imaging technique. The majority of targeted CT probe development has been pursued using metal-based nanoparticles due to their high atomic weight and therefore increased X-ray attenuation compared to the conventional iodine moiety.…”
Section: Targeted Nanoparticle Imaging Agentsmentioning
confidence: 99%
“…It has been reported that NMs having HDs in the sub-100-nm range possess higher tendency toward extravasating into tissue extracellular space [8,16,[45][46][47][48][49] by virtue of their sizes matching those of the pores on the vascular wall and as a result of microvascular permeability [13]. When administered AuNPs in the blood stream are extravasated into tumor extracellular space, endocytosis and clearance of the extracellular AuNPs in the tumor extracellular space would be initiated.…”
Section: Profiling Tumor Extracellular Aunps In Vivomentioning
confidence: 99%